2016
DOI: 10.1093/aje/kww010
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental-Variables Simultaneous Equations Model of Physical Activity and Body Mass Index

Abstract: We used full-system-estimation instrumental-variables simultaneous equations modeling (IV-SEM) to examine physical activity relative to body mass index (BMI; weight (kg)/height (m)2 ) using 25 years of data (1985/1986 to 2010/2011) from the Coronary Artery Risk Development in Young Adults (CARDIA) Study (n = 5,115; ages 18-30 years at enrollment). Neighborhood environment and sociodemographic instruments were used to characterize physical activity, fast-food consumption, smoking, alcohol consumption, marriage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…presence of weak instruments. 41 We also acknowledge that the retail food environment is only one risk factor for weight gain, and additional risk factors should be considered in future research, including factors related to food availability and prices in school, professional and recreational environments (i.e. not retail food outlets).…”
Section: Discussionmentioning
confidence: 99%
“…presence of weak instruments. 41 We also acknowledge that the retail food environment is only one risk factor for weight gain, and additional risk factors should be considered in future research, including factors related to food availability and prices in school, professional and recreational environments (i.e. not retail food outlets).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, Maydeu‐Olivares et al (2019) have confirmed that both 2SLS and IV‐SEM provide accurate coverage rates in the presence of endogeneity if the sample size is bigger than 500 observations. As long as 2SLS is practically susceptible under the weak instrument assumption, IV‐SEM allowing nonlinear estimation is robust (Meyer et al, 2016). In addition to the 2SLS and IV‐SEM models, a two‐stage regression model was regressed manually with a bootstrapping method.…”
Section: Methodsmentioning
confidence: 99%